Patriotism Values as Portrayed in Selected Poetry of Tennyson's Ulysses and Kaimuddin's Bula Malino : A Comparative Study - Hilmawati; Fathu Rahman; Herawaty Abbas (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Culture and literature differences raising birth of the uniqueness in every country that enriches the lives of the world community, including Butonese and English. This study aimed to compare patriotism values between the Selected Poetry of Tennyson‘s "Ulysses" and Kaimuddin‘s "Bula Malino" by using Comparative Study. This study identifies similarities and differences in the patriotism values implied in both of the poems. Through the Comparative French School Human Models and Heroes, this study analyzed the characterizations from both of the poems which possessed patriotism although the scope is differ. The concept of patriotism in Ulysses is related to the patriotic, loyalty, affectionate, sportsmanship, and heroism of a king, named Ulysses, to his kingdom, people, family, and his hobby. Whereas in Bula Malino, patriotism is shown by loyalty, affectionate, patriotic, and sportsmanship of Sultan MIK as the main character to his religious teachings.